2009
DOI: 10.1124/mol.109.058479
|View full text |Cite|
|
Sign up to set email alerts
|

Resveratrol Protects Mitochondria against Oxidative Stress through AMP-Activated Protein Kinase-Mediated Glycogen Synthase Kinase-3β Inhibition Downstream of Poly(ADP-ribose)polymerase-LKB1 Pathway

Abstract: Arachidonic acid (AA, a proinflammatory fatty acid) in combination with iron promotes excess reactive oxygen species (ROS) production and exerts a deleterious effect on mitochondria. We have shown previously that activation of AMP-activated protein kinase (AMPK) protects hepatocytes from AA ϩ iron-induced apoptosis. Resveratrol, a polyphenol in grapes, has beneficial effects mediated through SIRT1, LKB1, and AMPK. This study investigated the potential of resveratrol to protect against the mitochondrial impairm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
136
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(150 citation statements)
references
References 43 publications
10
136
2
2
Order By: Relevance
“…One reason could be that resveratrol might improve mitochondrial function; thereby more lactate could enter the next steps (citric acid cycle and oxidative phosphorylation) and produce a boost of ATP. This hypothesis is in agreement with other studies that also reported resveratrol to be able to protect cells from mitochondrial dysfunction and to increase the number of mitochondria [45][46][47].…”
Section: Resveratrol Induces a Downward Trend In Lactate Production Bsupporting
confidence: 93%
See 1 more Smart Citation
“…One reason could be that resveratrol might improve mitochondrial function; thereby more lactate could enter the next steps (citric acid cycle and oxidative phosphorylation) and produce a boost of ATP. This hypothesis is in agreement with other studies that also reported resveratrol to be able to protect cells from mitochondrial dysfunction and to increase the number of mitochondria [45][46][47].…”
Section: Resveratrol Induces a Downward Trend In Lactate Production Bsupporting
confidence: 93%
“…The powerhouse of energy production, mitochondrial function and number primarily impact on the supply of ATP [55]. Numerous studies in the literature also reported resveratrol protected cells from mitochondrial dysfunction [45][46][47]. Interestingly, resveratrol was found to increase the number of mitochondria in various cell lines and tissues, such as in Neuro2a cells [28], endothelial cells [56] and muscle [45].…”
Section: Discussionmentioning
confidence: 99%
“…recently, aMPK was shown to be involved in cellular homeostasis and emerged as a pivot point between cell survival and apoptosis (16)(17)(18). Previous studies have reported that aMPK activation regulates apoptosis in cancer cells via a signaling pathway that includes the up-regulation of p53 protein, activation of caspases, generation of roS and inhibition of the proteolytic cleavage of poly (adP-ribose) polymerase (ParP)-lKB1 (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol has been reported to have cytotoxic effects on various types of cancers (1). On the other hand, resveratrol has been shown to be apoptotic, autophagocytic, a radiotherapy-sensitizer, a cell cycle arrester, an inhibitor of ROS generation in mitochondria, and a regulator of p53 in many cancers (4,5,7,(18)(19)(20). One of the most important properties of resveratrol is that it has selective toxic effects on cancer cells and far less effect on normal, healthy cells (21).…”
Section: Discussionmentioning
confidence: 99%